Analysis Of The Effect Of Npl, Bopo And Ldr On Car With Roa As An Intervening Variable In Banking (Case Study: Conventional Commercial Banks on the Indonesia Stock Exchange (IDX) for the 2016-2021 Period) - Iqbal, Muhammad; Indrayono, Yohanes; Herdiyana, Herdiyana (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
Financial performance for bank financial institutions demonstrates how management is focused on managing the business and balancing the interests of shareholders, consumers, monetary authorities, and the general public whose activities are tied to banking. This study aims to provide a rationale for the relationship between Non-Performing Loans (NPL), Operating Costs on Operating Income (BOPO), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR) in Conventional Banks listed on the IDX for 2016–2021. 35 conventional commercial banks in Indonesia that will still be in operation by 2021 make up the population of this study. Purposive sampling was used in the sampling process, and 7 banks financial institutions were chosen as samples. The study's findings show that: (1) NPL has no significant impact on ROA; (2) BOPO has a substantial impact; (3) LDR has a significant impact; and (4) CAR factors have a large positive impact on ROA. The findings of this study show that the higher the CAR, the higher the ROA attained by the bank since the capital of the bank is better able to maintain the potential of the danger of losing its business, which also improves performance.